A Twist in Yeast: New Perspectives for Studying TDP-43 Proteinopathies in S. cerevisiae - Roberto Stella; Alessandro Bertoli; Raffaele Lopreiato; Caterina Peggion (Journal of Fungi)
TAR DNA-binding protein 43 kDa (TDP-43) proteinopathies are a group of neurodegenerative diseases (NDs) characterized by the abnormal accumulation of the TDP-43 protein in neurons and glial cells. These proteinopathies are associated with several NDs, including amyotrophic lateral sclerosis, frontotemporal lobar degeneration, and some forms of Alzheimer’s disease. Yeast models have proven valuable in ND research due to their simplicity, genetic tractability, and the conservation of many cellular processes shared with higher eukaryotes. For several decades, Saccharomyces cerevisiae has been used as a model organism to study the behavior and toxicity of TDP-43, facilitating the identification of genes and pathways that either exacerbate or mitigate its toxic effects. This review will discuss evidence showing that yeast models of TDP-43 exhibit defects in proteostasis, mitochondrial function, autophagy, and RNA metabolism, which are key features of TDP-43-related NDs. Additionally, we will explore how modulating proteins involved in these processes reduce TDP-43 toxicity, aiding in restoring normal TDP-43 function or preventing its pathological aggregation. These findings highlight potential therapeutic targets for the treatment of TDP-43-related diseases.